High-pressure processing enhances saltiness perception and sensory acceptability of raw but not of cooked cured pork loins—leveraging salty and umami taste - Bolumar, Tomas; Lohmayer, Regina; Peukert, Manuela; Thiemann, Kai; Münch, Siegfried; Brüggemann, Dagmar A. (Frontiers in Nutrition, 2024)
The salt (NaCl) content in processed meats must be reduced because of its adverse effects on cardiovascular health. However, reducing salt in meat products typically leads to a lower taste intensity and, thus, consumer acceptability. Industry interventions must reduce salt content while maintaining taste, quality, and consumer acceptability. In this context, high-pressure processing (HPP) has been proposed to enhance saltiness perception, though there are contradictory reports to date. The present work aimed to conduct a targeted experiment to ascertain the influence of HPP (300/600 MPa) and cooking (71 °C) on saltiness perception and sensory acceptability of meat products. HPP treatment (300/600 MPa) did enhance those two sensory attributes (approx. +1 on a 9-point hedonic scale) in raw (uncooked) cured pork loins but did not in their cooked counterparts. Further, the partition coefficient of sodium (PNa+), as an estimate of Na + binding strength to the meat matrix, and the content of umamitaste nucleotides were investigated as potential causes. No effect of cooking (71 °C) and HPP (300/600 MPa) could be observed on the PNa+ at equilibrium. However, HPP treatment at 300 MPa increased the inosine-5'-monophosphate (IMP) content in raw cured pork loins. Finally, hypothetical HPP effects on taste-mediating molecular mechanisms are outlined and discussed in light of boosting the sensory perception of raw meat products as a strategy to achieve effective salt reductions while keeping consumer acceptability.